The notorious daredevils: potential toxic levels of cyanide and heavy metals in cassava flour sold in selected markets—taken Oke Ogun Community, Oyo State as an example - Jacob, Omotoso Ayodele; Anuoluwa, Omotoso Elizabeth; Raimi, Morufu Olalekan (Frontiers in Sustainable Food Systems, 2023)
Pollution spread throughout terrestrial and aquatic ecosystems, and many remain transported around the globe by air transport. Furthermore, food as well as production chains remain dispersed through the global economy. Thus, the current study examined the potentially harmful amounts of cyanide as well as trace metals in cassava flour sold in Oke Ogun community township markets. Its goal was to quantify the degrees of Lead, Cyanide, Arsenic and Chromium, evaluate their health impacts on customers, and evaluate WHO-allowable dietary quantities. Using a stratified sampling strategy, five township markets were visited to obtain samples of finely ground fermented cassava flour (Kishi, Igbeti, Igboho, Iseyin, and Shaki). The materials were properly digested before being examined with an Atomic Absorption Spectrophotometer (AAS). Lead (0.028–0.053 mg/L), Cyanides (0.010–0.018 mg/L), Chromium (0.034–0.065 mg/L) and Arsenic (0.006–0.012 mg/L), were the results obtained. At conclusion, due to the lower content of these metals, the cassava flour sold in Oke Ogun community markets is safe as well as appropriate for human utilization, with no nutritional risk consequences. As a result, it is advised that cassava flour marketed be closely checked and assessed on a continuous basis. Therefore, regular monitoring of toxic metals in Nigeria is strongly advised in order to avoid a significant environmental and public health issue.